Extensive stimulus repetition leads older adults to show delayed functional magnetic resonance imaging adaptation - Miyakoshi, Makoto (2013)
We investigated whether extensive repetition can diminish age-related differences between younger and older adults in functional magnetic resonance adaptation (fMR-A). Datasets were obtained from 26 younger and 24 older healthy adults presented with two scenes that repeated 20 times amongst other novel scenes during fMRI scanning. The average cortical responses to the first eight (Repetitions 1-7) and the last eight (Repetitions 12-19) presentations out of 20 were compared within each group. Younger adults showed similar levels of fMR-A in both repetition sets. Conversely, older adults did not show reliable fMR-A in Repetitions 1-7, but they did in Repetitions 12-19; subtracting the latter from the former revealed a significant effect within left inferior occipital, left lingual, and the posterior part of fusiform gyrus. We concluded that cortical responsiveness in older adults are compromised, but extensive repetition can lead older adults to show a delayed but closer level of fMR-A compared to younger adults.